A Survey of Physical Therapists' Attitudes and Practice Patterns Regarding Intervention During a Red Blood Cell Transfusion. Issue 4 (December 2016) - Rosenfeldt, Anson B.; Pilkey, Lauren M.; Butler, Robert S.
Abstract : Purpose: Blood cell transfusions occur in approximately 12% of individuals who are hospitalized and undergo a procedure. There is a lack of evidence to guide physical therapists (PTs) and physical therapist assistants (PTAs) in the delivery of physical therapy services to individuals receiving an red blood cell (RBC) transfusion. The purpose of this survey was to determine current practice patterns in this patient population. Methods: An electronic survey was distributed to PTs and PTAs across the state of Ohio. Results: Of the 262 respondents, 54.8% of individuals felt comfortable delivering physical therapy services to individuals receiving an RBC transfusion. PTs with a doctoral degree and those who worked in an inpatient hospital or long-term acute care setting were more likely to treat. Respondents required an average minimum hemoglobin (Hb) concentration of 6.9 g/dL to deliver physical therapy services to individuals who were anemic and receiving an RBC transfusion. Nine-point-two percent of respondents reported that their institution had a policy regarding the delivery of physical therapy services during an RBC transfusion. Conclusion: Responses revealed variability in practice patterns among PTs and PTAs regarding comfort level, likelihood to treat, Hb concentration, institutional policies, and perceived barriers pertaining to the delivery of physical therapy services to individuals receiving an RBC transfusion. There is a need for further research on this topic to guide therapists in the clinical decision-making process.